Modelo de colapso en piscina (2016)
"I would say all started with a point. Perhaps a point that contained infinitely other points. There was no order. Only infinities that lasted. Fluctuations from the instabilities. Nothing was the same, And what was not nothing will be different. Nothing will be forever, And maybe what is not nothing will end. What in the natural is homogeneous? What in the natural is geometric? What in the natural is square? This project comes from the aesthetic, conceptual and formal fixation that I have on the grids present in our daily lifes. In this project I focus mainly on the grids formed by the tiles in the pools and how these are deformed by the water. A small act that leads to question about geometry, change and time in everyday scenarios that we must reevaluate, In a world where everything tends to curves and distortion." -- Tomado del Formato de Documento de Grado.